Cathodic material effect on electron acceptance towards bioelectricity generation and wastewater treatment. (December 2016) - Modestra, J. Annie; Chiranjeevi, P.; Mohan, S. Venkata
Abstract: Influence of cathode material on electron accepting conditions during the treatment of recalcitrant pharmaceutical wastewater (PWW) was comparatively evaluated at different organic loads (3, 6, 9 and 15 g/l) in three bioreactors. Two bio-electrochemical treatment systems employed with different electrode materials viz., BET-SS (graphite as anode and stainless steel (SS) as cathode) and BET-G (graphite as both anode and cathode) were evaluated for PWW degradation and bioelectricity generation in comparison to conventional anaerobic treatment (AnT). BET-G exhibited high bioelectrogenic activity than BET-SS, elucidating the impact of varied cathode material. High cathode potential necessary for effective reduction at cathode were observed with graphite-cathode than SS-cathode which are crucial for treatment and power generation. Ohmic losses ascribed to electrode material interference were relatively high in BET-SS in comparison to BET-G. Graphite-cathode exhibited high electron acceptance conditions leading to higher pollutant removal along with organic fraction degradation, bio-electrogenesis and inorganic salts removal, when compared to SS-cathode. Placement of electrode assembly while operating BET with different electrode materials is proved to be significant for treatment and bioelectricity production. Efficient electron accepting conditions and high cathode potential in BET-G proved graphite as promising cathode material over SS for the treatment of PWW. Highlights: Electrode materials influenced treatment efficiency and bioelectricity generation. Ohmic losses were predominant with SS-cathode in comparison to graphite. Reactor configuration is crucial while choosing dissimilar electrode materials. Graphite as cathode depicted high electron acceptance than SS.